Palauan Reference Grammar - Josephs, Lewis S. (University of Hawai'i Press, 2018)
The Palauan Reference Grammar offers a comprehensive description of the language that will interest speakers of Palauan and linguists alike. Although the linguistic phenomena of Palauan are often extremely complex, special efforts have been made to keep explanations as simple and clear as possible while capturing the essential phonological and grammatical principles unique to the language. Material is presented in order of difficulty, with an analysis at each stage. By mastering each level as he goes along, the general reader should have little difficulty in grasping later analyses of more complex material. Some information of a highly technical nature is included for readers with a background in linguistics. These discussions are marked with an asterisk and can be disregarded by the nontechnical reader without appreciable loss of understanding. Learning is facilitated by extensive cross-referencing, a list of phonetic and orthographic symbols, a glossary of relevant linguistic terms, a brief bibliography, and an index.